2017
DOI: 10.1007/s40477-017-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ultrasonography and computed tomography in assessing thyroid cartilage invasion in laryngeal and hypopharyngeal cancers

Abstract: US and CT have high diagnostic performance in evaluating thyroid cartilage invasion. US is more sensitive than CT in diagnosing invasion of the thyroid cartilage; however, the difference is not statistically significant. US can be used to solve the diagnostic dilemma of the presence or absence of cartilage invasion when CT is inconclusive, as CT is more widely used in staging laryngeal and hypopharyngeal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…A statistically significant improvement in the specificity of detection of paraglottic space invasion was seen with ultrasound. Dhoot et al performed a similar study but with pathological confirmation of thyroid cartilage invasion post-laryngectomy (24). A trend towards improved sensitivity in detection of thyroid cartilage invasion was also noted for ultrasound (98%) compared to CT (91%).…”
Section: Conventional Radiotherapymentioning
confidence: 88%
See 1 more Smart Citation
“…A statistically significant improvement in the specificity of detection of paraglottic space invasion was seen with ultrasound. Dhoot et al performed a similar study but with pathological confirmation of thyroid cartilage invasion post-laryngectomy (24). A trend towards improved sensitivity in detection of thyroid cartilage invasion was also noted for ultrasound (98%) compared to CT (91%).…”
Section: Conventional Radiotherapymentioning
confidence: 88%
“…Dhoot et al. performed a similar study but with pathological confirmation of thyroid cartilage invasion post-laryngectomy ( 24 ). A trend towards improved sensitivity in detection of thyroid cartilage invasion was also noted for ultrasound (98%) compared to CT (91%).…”
Section: Conventional Radiotherapymentioning
confidence: 99%
“…Further experience with the TLUSG examination can pave the way for new prospects of laryngeal ultrasound use in ENT Departments like the ultrasound-guided identification of the cricothyroid membrane in the management of cricothyrotomy [ 20 , 21 ], the assessment of laryngeal pathologies in children including dysphonia and stridor [ 22 ] or a diagnostic complement to laryngoscopy and tomography in patients with laryngeal cancer [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, other studies even reported higher diagnostic accuracy of CT for detection of thyroid cartilage invasion. Dhoot et al, [14] evaluated the adequacy of CT in the assessment of thyroid cartilage invasion in patients with airway cancer. Sixtytwo consecutive patients underwent CT to stage laryngeal (n=27) or hypopharyngeal (n=35) cancer in this prospective study.…”
Section: Discussionmentioning
confidence: 99%